BODY, MISOGYNY AND RELIGION IN SWEAR WORDS: - Knyazyan, Anna; Artoni , Linda (Armenian Folia Anglistika, 2023)
The main focus of this article is on the use of the most common English, Italian and Russian swear words. The language of swearing has been taboo for many years considering that swear words have always been regarded as offensive, inappropriate and unacceptable in any social context. Profanity reflects not only our emotions but also our values, taboos, and prejudices. It is evident that different cultures have distinct rules and perceptions surrounding cursing – the most powerful words that can express both positive and negative emotions; therefore they are actively used by people of all ages, genders, social statuses and languages. Taking into consideration that swear words and obscenity are common in all languages, there are many similarities and differences between them and their rendition of obscenity. Even though the topic of swearing has been neglected for many years, it is a quite complex one and many discussions and different interpretations can be made. That is to say, the formation of swear words, their functions, degrees of offensiveness, different typologies and classifications are investigated through a comparative method, to conclude what common taboos are shared by these three cultures.